Green infrastructure can promote plant functional connectivity in a grassland species around fragmented semi‐natural grasslands in NW‐Europe. Issue 10 (7th September 2022) - Plue, Jan; Kimberley, Adam; Bullock, James M.; Hellemans, Bart; Hooftman, Danny A. P.; Krickl, Patricia; Leus, Leen; Peeters, Gerrit; Poschlod, Peter; Traveset, Anna; Volckaert, Filip; Cousins, Sara A. O.; et al.
Abstract : Species may benefit from green infrastructure, i.e. the network of natural and anthropogenic habitat remnants in human‐dominated landscapes, if it helps isolated populations in remaining habitat patches to be functionally connected. The importance of green infrastructure is therefore increasingly emphasized in conservation policy to counter biodiversity loss. However, there is limited evidence, particularly in plants, that green infrastructure promotes functional connectivity, i.e. supports the colonization of habitat patches across a landscape. We applied landscape genetics to test whether the green infrastructure supports structural and functional connectivity in the grassland perennial Galium verum, in 35 landscapes in Belgium, Germany and Sweden. We used multivariate genetic clustering techniques, nestedness analyses and conditional inference trees to examine landscape‐scale patterns in genetic diversity and structure of plant populations in the green infrastructure surrounding semi‐natural grasslands. Inferred functional connectivity explained genetic variation better than structural connectivity, yielding positive effects on genetic variation. The road verge network, a major structural component of the green infrastructure and its functional connectivity, most effectively explained genetic diversity and composition in G. verum . Galium verum ramets occupying the surrounding landscape proved to be genetic subsets of focal grassland populations, shaping a nested landscape population genetic structure with focal grasslands, particularly ancient ones, harbouring unique genetic diversity. This nested pattern weakened as road network density increased, suggesting road verge networks enable high landscape occupancy by increased habitat availability and facilitates gene flow into the surrounding landscape. Our study proposes that green infrastructure can promote functional connectivity, providing that a plant species can survive outside of core habitat patches. As this often excludes habitat specialist species, conservation practice and policy should primarily focus on ancient, managed semi‐natural grasslands. These grasslands both harbour unique genetic diversity and act as primary gene and propagule sources for the surrounding landscape, highlighting their conservation value.